Hypolipidaemic effects of synbiotic yoghurt in rabbits. (10th June 2019) - Sarfraz, Farkhandah; Farooq, Umar; Shafi, Afshan; Hayat, Zafar; Akram, Kashif; Rehman, Hafeez‐Ur
Abstract : The hypolipidaemic effects of synbiotic yoghurt prepared using Lactobacillus acidophilus, fructooligosaccharide (FOS) and isomaltooligosaccharide (IMOS) were assessed through biological study. Hyperlipidaemia‐induced rabbits were fed on a diet containing different levels of synbiotic yoghurt, and the blood of the animals was analysed for lipid profile on a weekly basis. There were significant reductions in total cholesterol (124.00 ± 7.10 mg/dL), triglycerides (155.00 ± 8.88 mg/dL), low‐density lipoprotein levels (13.27 ± 0.76 mg/dL) and very low‐density lipoprotein levels (57.04 ± 3.27 mg/dL), whereas high‐density lipoprotein levels (53.70 ± 0.35 mg/dL) were increased. On the basis of these results, it was concluded that the synbiotic yoghurt possessed a significant hypolipidaemic potential.